Functional state of cardiomyocyte mitochondria in malignant process in presence of comorbid pathology in experiment - E. M. Frantsiyants; I. V. Neskubina; N. D. Cheryarina; E. I. Surikova; A. I. Shikhlyarova; V. A. Bandovkina; L. A. Nemashkalova; I. V. Kaplieva; L. K. Trepitaki; P. S. Kachesova; I. M. Kotieva; M. I. Morozova; et al. (Южно-Российский онкологический журнал, 2021)
Purpose of the study. An analysis of indices of free radical oxidation and respiration of mitochondria of heart cells in a malignant process in presence of diabetes mellitus and chronic neurogenic pain in experimental animals.Materials and methods. The study included outbred female rats (n=32) and С57ВL/6 female mice (n=84). Experimental groups of rats were: intact group 1 (n=8), control group 1 (n=8) with diabetes mellitus (DM), comparison group 1 (n=8) with standard subcutaneous transplantation of Guerin’s carcinoma, main group 1 (n=8) with Guerin’s carcinoma transplanted after 1 week of persistent hyperglycemia. Experimental groups of mice were: intact group 2 (n=21), control group 2 (n=21) with a model of chronic neurogenic pain (CNP), comparison group 2 (n=21) with standard subcutaneous transplantation of melanoma (B16/F10), main group 2 (n=21) (CNP+B16/F10) with melanoma transplanted 3 weeks after the CNP model creation. Heart mitochondria were isolated by differential centrifugation. Levels of cytochrome C (ng/mg of protein), 8-hydroxy-2'-deoxyguanosine (8-OHdG) (ng/mg of protein), and malondialdehyde (MDA) (μmol/g of protein) were measured in mitochondrial samples by ELISA. Statistical analysis was performed using the Statistica 10.0 program.Results. DM in rats upregulated 8-OHdG by 6.3 times and MDA by 1.9 times (р=0.0000) and downregulated cytochrome C by 1.5 times (р=0.0053) in heart cell mitochondria, compared to intact values. DM+Guerin’s carcinoma in rats increased 8-OHdG by 14.0 times and MDA by 1.7 times (р=0.0000) and decreased cytochrome C by 1.5 times (р=0.0000), compared to intact values. CNP in mice did not affect the studied parameters in mitochondria of the heart. CNP+B16/F10 in mice increased 8-OHdG by 7.1 times and MDA by 1.6 times (р=0.0000) and decreased cytochrome C by 1.6 times (р=0.0008).Conclusions. Comorbidity (diabetes mellitus, chronic neurogenic pain) together with malignant pathology aggravates mitochondrial dysfunction of heart cells with destabilization of the respiratory chain mediated by free radical oxidation processes.